Effect of Combination Training Shuttle Runn and Zig-zag Run on the Agility of Male and Female Karate Athletes at the State University of Malang - Nawawi, Muhammad; Adriana, Oliviana; Ratna, Ardhiyanti Puspita (Fakultas Pendidikan Olahraga dan Kesehatan, Universitas Pendidikan Indonesia, 2023)
Karate is a branch of achievement sports that has a Kumite competition number. There are two athletes in the Kumite category in a karate match who face each other and must have agility when attacking and defending. The purpose of this study was to understand the effect of combination training of Shuttle Run and Zig-zag Run on the agility of male and female karate athletes at State University of Malang. This pre-experimental study used the One Group Pretest-Posttest Design. The population used was karate athletes at Malang State University with a total of 24 samples divided into male athletes and female athletes. The agility of karate athletes was assessed using the Illinois agility test at the pretest and post-test. Based on the analysis of the Paired Samples T Test, it showed that the combined Shuttle Run and Zig-zag Run exercises had a significance = 0.00 (p 0.05) for male athletes, while a significance value = 0.00 (p 0.05) for female athletes. Based on the findings of this study, the combined training of Shuttle Run and Zig-zag Run is effective in increasing the agility of male and female karate athletes at the State University of Malang